DESIGN OF STORAGE LAYOUT FOR PROTECTOR MATERIAL (FAST MOVING) WITH CLASS BASED STORAGE METHOD AT RAW MATERIAL WAREHOUSE JEPARA PT DSV SOLUTIONS INDONESIA (SEMARANG BRANCH) - Cindy Rahmawaty; Mashudi Mashudi (International Journal of Artificial Intelligence for Digital Marketing, 2024)
PT DSV Solutions Indonesia Semarang Branch is a 3PL company engaged in warehousing logistics. The current condition is that the protector material storage still uses a randomized storage method and the GR (Good Receiving) method which rearranges the boxes into pallets. The current layout causes a fairly high displacement distance and has an impact on high material handling costs and the size of the blocks on the shelves that make the GR method long. The purpose of this study is to design a storage layout for protector (fast moving) materials using the class-based storage method to determine changes in displacement distance, material handling costs, and work efficiency and performing the GR (Good Receiving) process. Researchers used descriptive qualitative research methods with observation, interviews, and documentation. The results showed the total distance of the initial displacement of the protector material was 16,172,250 m and the Material Handling Cost was Rp 109,971,300 and the GR process did not require rearrangement into pallets. The output of this research is that it can reduce the total distance of moving the protector material and streamline the distance of movement by 56% and streamline the Material Handling Cost by 56%. In the changed GR (Good receiving) method, it can raise the beam on the level 3 shelf, by 1.5m. The material protector storage layout can be said to be efficient using the class-based storage method when compared to the initial storage layout.